Beyond art technical sources: understanding colour production in Andalusi texts - Miranda, Ana (2025)
The study of colour production in al-Andalus has been mostly directed towards art technical documentary sources, such as al-Qalalūsī’s Tuḥaf al-Ḫawāṣ (The Treasures of the Select), the 13th century Andalusi instructional book. The focus of the said research falls on the ingredients and procedures to create colour. However, the technical-centred approach tends to overlook social, economic, and cultural aspects of colour-making, such as the social perception towards dyers, prices, colour etiquette, besides the context under which such manuals were written. Other types of texts – such as geographical, normative, technical, and epistolary – can help to fulfil such gaps, by providing information regarding the production, commerce, transportation, symbolism, and further uses of raw materials used in colour production, such as alum, cinnabar, and indigo. A multifaceted approach which combines the analysis of different types of coeval sources, primarily Andalusi, can contribute for a more comprehensive insight on colour production in al-Andalus.